Equality Comparator question

Discussion in 'Homework Help' started by onlylonely, Sep 4, 2005.

  1. onlylonely

    Thread Starter New Member

    Sep 4, 2005
    4
    0
    anyone know how to change this expression
    E=A1'A0'B1'B0'+A1'A0B1'B0+A1A0'B1B0'+A1A0B1B0

    TO one that uses XOR gates,inverter and 1 other gate...

    I have an answer:(A1'B1+A1B1')'(A0'B0+A0B0')'

    but i didn't know the procedure.....

    can someone expert help me....or give me some guide to do it...

    THANNKS A LOTS!!
     
  2. dragan733

    Senior Member

    Dec 12, 2004
    152
    0
    E=A1'A0'B1'B0'+A1'A0B1'B0+A1A0'B1B0'+A1A0B1B0=
    A1'B1'(A0'B0'+A0B0)+A1B1(A0'B0'+A0B0)=
    (A1'B1'+A1B1)(A0'B0'+A0B0)=
    (A1'B1+A1B1')'(A0'B0+A0B0')' because
    (A'B'+AB)=(A'B+AB')'

    proof:
    (A'B+AB')'=(A'B)'(AB')'=(A+B')(A'+B )=AA'+AB+A'B'+BB'=
    0+AB+A'B'+0=
    AB+A'B'=A'B'+AB
     
Loading...